1989 - McDermid, Val (McDermid, Val. Allie Burns novel., 2022)
"A riveting thrill ride of a novel from a captivating new series, 1989 confirms internationally bestselling author Val McDermid as one of crime fiction's true masters. It's 1989 and journalist Allie Burns is growing up. Older and maybe wiser than the hustling young hack we met in 1979, she's running the northern news operation of the Sunday Globe, chafing at losing her role in investigative journalism and at the descent into the gutter of the UK tabloid media. But there's plenty to keep her occupied. The year begins with the memorial service for the victims of the bombing of Pan Am Flight 103, but Allie has barely filed her copy when she stumbles over a story about HIV/AIDS that will shock her into a major change of direction. The world of newspapers is undergoing a revolution, there's skullduggery in the medical research labs and seismic rumblings behind the Iron Curtain. When murder is added to this potent mix, Allie will be called upon to chase a story that will take her further afield than she'd ever planned, and force her to question all her old certainties"--